Pengembangan Video Pembelajaran Fisika Interaktif Pada Materi Tekanan Hidrostatis - Purwanti, Popi; Astuti, Irnin Agustina Dwi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
This study aims to develop learning media in the form of learning videos with its subject is about hydrostatic pressure. This video development method is made as easy as possible while maintaining the worthiness of this video for use in learning. This video development uses several tools, namely PC, pen tablet, OBS Studio application, and Paint 3D. In addition, the content of this learning video can also involve books or worksheets by using additional applications such as the Snipping Tool, CamScanner, virtual practicum web, and or others as long as these additions can be displayed on the PC screen. This research method uses a 4D model (Define, Design, Development, Disseminate). This learning video has been said to be eligible to use based on validation from material, media and language experts, namely with an average total score of 72%, 73%, and 73%, which means that all three are in good eligibility criteria. This learning video was also tested to students with an average score of 77% which means the eligibility criteria are good.